Cost Analysis of Outpatient Mental and Behavioral Disorders Due to Psychoactive Substance Use: A study of four community and two general hospitals in Thailand - Utoomporn Wongsin; Passakorn Suanrueang (ACHSM, 2023)
This cost analysis study gathered cost information from four community hospitals and two general hospitals in the fiscal year 2014, including service data, hospital statistics, and financial information. The study aimed to analysis and estimate the treatment costs of outpatient mental and behavioral disorders (MBDs) due to psychoactive substance use, provided at community and general hospitals in Thailand. We used ICD-10 codes, F10-F19, to handle the diagnosis codes of MBDs due to psychoactive substances and cost analysis. The unit cost per OPD visit was analyzed according to the cost analysis guidelines of the Ministry of Public Health, Thailand, using two procedures: a traditional method and a cost-to-charge ratio. The great majority of service expenses were labour costs (53%), followed by material costs (42%) and capital costs (6%). The unit cost per OPD visit for substance use disorders (SUD) in 2014 ranged between 172 and 762 THB. It was adjusted by the inflation rate to estimate the cost for 2021. The costs were growth in the range of 204 to 905 THB. The median cost estimate in 2021 from four community hospitals and two general hospitals, each accounting for 396 and 769 THB, respectively. The unit SUD visit costs of OPD from these six hospitals are quite close to the unit costs of the drug treatment centers. The greatest proportion of total service expenses was labor costs. Accordingly, human resources are believed to be a crucial challenge that needs to be considered and planned to deliver successful services.   Notably, these hospitals were selected by purposive sampling and might not be representative of each hospital type. More hospitals should, therefore, be recruited in further research to represent the actual cost by hospital type.